Capture-aware bit-detecting M-ary tree protocol for RFID tag identification - Lijuan ZHANG; Mingqiu FAN; Lei LEI; Yong WANG; Daishu YUAN (Tongxin xuebao)
In passive radio frequency identification (RFID) systems, the capture effect may occur that the reader is possible to successfully decode the strongest signal when multiple tags reply simultaneously.In this situation, the weaker signals will be covered resulting in a tag hidden problem which greatly affects the system performance.To solve the problem, a bit-detecting M-ary tree (BMT) protocol was proposed.First, a bit-detecting tag number estimation method was proposed to estimate the number of tags and group them with a few slots.Next, an M-ary tree protocol was developed to eliminate all the idle slots and identify tags quickly.At the same time, a hash muting strategy was given to mute the identified tags and label the hidden ones with small communication cost.Both theoretic analysis and simulation results demonstrate that BMT can effectively reduce the identification delay by at least 15%.